Avaliação das habilidades cognitivas em praticantes idosos de karate-dō de longa data - Lopes Filho, Brandel José Pacheco (2019)
Introduction: physical exercise and martial arts can influence the cognitive performance of the old people, acting as important tools to prevent cognitive impairments and to increase intervention strategies. Martial arts, especially Karate-Dō, are considered wide-ranging types of exercise, which in addition to bringing benefits to physical health, contribute to stimulate motor and cognitive skills, improve the quality of life and emotional aspects of their practitioners. Objective: to verify the performance of cognitive functions and cognitive reserve capacity in elderly people practicing Karate-Dō in long term. Methods: a cross-sectional and comparative study was carried out with 99 elderly people divided into three groups: Long-time Karate-Dō Group (n=37), Sedentary Group (n=41) and Social Activities Group (n=21). The subjects respond to a sociodemographic questionnaire, a battery of cognitive tests (evaluation of time-space orientation, recording, attention, calculation, evocation, language and executive functions) and scales of subjective cognitive complaints and humoral (anxiety and depression). The Sedentary Group did not perform any physical activity and the Social Activities Group participated in varied social activities, but not physical exercise. Data analysis was performed with descriptive and inferential statistics. Data distribution was verified using the Kolmogorov-Smirnov test. Differences between groups were investigated by the Kruskal-Wallis test and Mann-Whitney U test. Results: in the comparison between groups, the Sedentary Group individuals scored lower on the Cognitive Reserve Questionnaire than in the Social Activities Group (p=0.012) and the Long-time Karate-Dō Group (p≤0.001). obtained similar scores (p=0.104) in the Cognitive Reserve Questionnaire. The Sedentary Group scored higher on the motivation subscale of GDS-15 when compared to the Social Activities Group (p=0.016). Conclusions: Karate-Dō practice seems to bring in long term benefits to cognitive reserve capacity to healthy seniors. At the same time, it was evidenced that social activities seem to increase the capacity of cognitive reserve and are related to the reduction of depressive symptoms.